EFEKTIVITAS SABUN ALAMI TERHADAP WARNA BATIK - Laela, Euis; Isnaini, Isnaini; Rufaida, Evi Yuliati; Sayogo, Rahmat (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2018)
This research was conducted to determine the effectiveness of natural soap on the color of batik. Natural soap used is lerak fruit, liquid soap from lerak and liquid soap from mangroves. The method used is comparing the test results using standard soap (AATTC WOB) required in the SNI ISO 105-C06: 2010 method with natural soap. The results showed that the color change values using standard soap, lerak fruit, liquid soap from lerak and liquid soap from mangrove plants were the same on a 4-5 scale. The color desecration value of cotton fiber for standard soap, lerak fruit, liquid soap from lerak on scale 4. The desecration value of cotton fiber for liquid soap from mangroves on a 4-5 scale is better than the standard AATCC soap. The value of the color change between natural soap and standard soap is not significantly different. Then natural soap can be used as a batik washing solution.